2020
DOI: 10.1111/ejn.15045
|View full text |Cite
|
Sign up to set email alerts
|

Locus coeruleus in memory formation and Alzheimer's disease

Abstract: The locus coeruleus (LC) was described in the 18th century by Félix Vicq d'Azyr as a blue spot located in the dorsal-rostral pons of freshly dissected brain. It contains densely packed medium-sized neurons that innervate the entire brain with unmyelinated projections. The LC provides relatively dense innervations to the thalamus and amygdala,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 138 publications
(174 reference statements)
1
25
0
1
Order By: Relevance
“…This supports a previously theorized buffering role of the LC, due to its high lifetime noradrenergic turnover and neuronal density, in protecting against the detrimental effects of accumulating AD-related pathology (Clewett et al 2015;Robertson 2013). Although the exact role of brainstem degeneration in cognitive dysfunction is not wellunderstood, degeneration of the LC appears to be related to cognitive function in normal aging (Dahl et al 2019;Langley et al 2020) and correlates with cognitive abilities and pathological protein accumulation in animal models of AD (Chalermpalanupap et al 2017;James et al 2020;Kelberman et al 2020). Of note, we found attenuated brainbehavior relationships in the biomarker-confirmed MCI due to AD group compared to the overall MCI group, likely due to the smaller sample size.…”
Section: Discussionsupporting
confidence: 82%
“…This supports a previously theorized buffering role of the LC, due to its high lifetime noradrenergic turnover and neuronal density, in protecting against the detrimental effects of accumulating AD-related pathology (Clewett et al 2015;Robertson 2013). Although the exact role of brainstem degeneration in cognitive dysfunction is not wellunderstood, degeneration of the LC appears to be related to cognitive function in normal aging (Dahl et al 2019;Langley et al 2020) and correlates with cognitive abilities and pathological protein accumulation in animal models of AD (Chalermpalanupap et al 2017;James et al 2020;Kelberman et al 2020). Of note, we found attenuated brainbehavior relationships in the biomarker-confirmed MCI due to AD group compared to the overall MCI group, likely due to the smaller sample size.…”
Section: Discussionsupporting
confidence: 82%
“…There is evidence from neuroimaging studies in AD patients that LC degeneration affects functional connectivity between memoryrelevant structures such as the parahippocampus and the LC (Jacobs et al, 2015) leading to memory dysfunction. It is hypothesized that memory functions are impaired in patients with AD due to LC degeneration entailing consecutive dysfunction of cellular correlates of long-term memory formation (James et al, 2020). Animal models have revealed the LC's relevant role in hippocampal long-term plasticity in different hippocampal subregions such as the dentate gyrus and CA1 region (Lemon et al, 2009;Hansen and Manahan-Vaughan, 2015a,b).…”
Section: Noradrenergic Mechanisms Inducing Psychiatric Symptoms In Prmentioning
confidence: 99%
“…The locus coeruleus (LC) is the small, bilaterally shaped structure in the brainstem located in the pons that contributes to cognitive functions (Berridge and Waterhouse, 2003;Sara and Bouret, 2012;Grueschow et al, 2020;James et al, 2020;Poe et al, 2020). The LC is the main location of a highly flexible, adaptable noradrenergic system projecting in many cortical and subcortical brain regions, thus explaining its highly relevant function in humans in everyday life, and essential for us humans as feeling and thinking beings.…”
Section: Introductionmentioning
confidence: 99%
“…The locus coeruleus, which provides NE input to widespread regions of the brain, has repeatedly been shown to degenerate in AD [48], suggesting a noradrenergic deficit in this disorder. A previous publication has suggested, however, that elevated noradrenergic signaling may in some cases be an etiological factor in AD [11], and more recent papers have also suggested that synaptic NE may be elevated or at least not diminished in spite of degeneration of the locus coeruleus, especially in early stages of the disease [4,5,12].…”
Section: Alzheimer's Diseasementioning
confidence: 99%